Study of hydrodynamic behaviour in bubble columns and external loop airlift reactors through analysis of pressure fluctuations - Vial, C.; Camarasa, E.; Poncin, S.; Wild, G.; Midoux, N.; Bouillard, J. (Chemical engineering science, 2000)
Recent methods of regime identification based on pressure fluctuations analysis have been applied both in a bubble column and an external loop airlift reactor with several spargers. Their ability to determine regime transition and to extract regime features is compared. A new method based on the auto-correlation function is proposed. This method is shown to be simple and efficient. It also provides quantitative information about the characteristic time and the axial dimension of the flow structure in the prevailing regime.